Pengaruh Occupational Self-Efficacy Terhadap Work Engagement Pada Karyawan PT BRN - Azmi Fauziyyah; Agus Budiman (UNISBA Press, 2022)
Abstract. Occupational self-efficacy is a belief about onself as a powerful determinants of performance (Pethe et al., 1999). Work engagement is positive emotions related to work characterized by vigor, dedication, and absorption (Schaufeli et al., 2002). The COVID-19 Pandemic affects employees on their work engagement level. This study aims to investigate the effect of occupational self efficacy on work engagement by using the job demands-resources (JD-R) model. The participants of this research were 46 employees of PT BRN. The method used in this study is quantitative research with simple linear regression analysis. The measuring instrument used in this study is OSE Scale from Pethe, et al. and UWES from Schaufeli & Bakker. The finding shows that 60% employees have a low level of occupational self-efficacy and 57.78% employees have a low level of work engagement. According to the regression analysis results, occupational self-efficacy has a significant effect of 51.7% that contributed on work engagement. Abstrak. Occupational self-efficacy adalah keyakinan seseorang pada kemampuan dan kompetensinya dalam melakukan suatu pekerjaan (Pethe et al., 1999). Work engagement adalah emosi positif yang berkaitan dengan pekerjaan yang ditandai oleh adanya vigor, dedication, dan absorption (Schaufeli et al., 2002). Pandemi COVID-19 mempengaruhi karyawan pada tingkat work engagement. Penelitian ini bertujuan untuk mengetahui pengaruh occupational self-efficacy terhadap work engagement dengan menggunakan model job demands-resources (JD-R). Partisipan dalam penelitian ini adalah 46 karyawan PT BRN. Metode yang dignakan dalam penelitian ini adalah penelitian kuantitatif dengan menggunakan analisis regresi linear sederhana. Alat ukur yang digunakan dalam penelitian ini adalah skala OSE dari Pethe, et al. dan UWES dari Schaufeli & Bakker. Hasil penelitian menunjukkan bahwa 60% karyawan memiliki occupational self-efficacy yang rendah dan 57.78% karyawan memiliki work engagement yang rendah. Berdasarkan hasil analisis regresi, occupational self-efficaacy memiliki pengaruh signifikan sebesar 51.7% yang memberikan kontribusi terhadap work engagement.